Environmentally Friendly and Facile Solid-State Synthesis of Nanostructured Cobalt Ferrites - Nguyen, Khoa Dang; Tran, Khoa Dang; Pham, Van Thi Tuong; Le, Ha Vu (Universitas Gadjah Mada, 2025)
In this study, a simple and solvent-free grinding method was employed to produce nanostructured cobalt ferrites (CoFe2O4). Their morphology and textural properties were notably found to be impacted by the calcination. Notably, the prepared material calcinated at 250 °C exhibited high mesoporosity with a surface area of 186 m2 g−1 and a pore size of approximately 3.2 nm, while the highly crystalline CoFe2O4 with sparse pore structure would tend to be more favorable as increasing calcination temperatures. At 550 °C, the CoFe2O4 material specifically formed a well-defined shape, albeit with non-uniform particle sizes ranging from 40 to 80 nm. These distinct nanostructures were completely lost upon calcination at 900 °C, resulting in a bulk CoFe2O4 with a very high crystallinity. Furthermore, the study also investigated the influence of polyvinylpyrrolidone (PVP) on the structure and morphology of as-prepared CoFe2O4. It was observed that PVP could mitigate sintering, leading to the increase in the surface area of CoFe2O4 calcined at 550 °C due to the decrease in nanoparticle size.